Penta-fluoro-phenyl (3R,4R,5S)-5-{[(3R,4R,5S)-5-azido-methyl-3,4-dimeth-oxy-2,3,4,5-tetra-hydro-furan-3-carboxamido]-meth-yl}-3,4-dimeth-oxy-2,3,4,5-tetra-hydro-furan-3-carboxyl-ate. - Simone, M; Edwards, A; Parker, S; Tranter, G; Fleet, G; Watkin, D (2010)
The title compound, C(22)H(25)F(5)N(4)O(9), is a stable penta-fluoro-phenyl ester inter-mediate in the synthesis of novel homo-oligomeric structures containing branched carbon chains. The structure is epimeric to the previously characterized dimeric penta-fluoro-phenyl ester with stereochemistry (3R,4R,5R), which was synthesized using d-ribose as starting material. The crystal structure of the title mol-ecule removes any ambiguities arising from the relative stereochemistries of the six chiral centres. Two hydrogen bonds, bifurcating from the NH group, stabilize the crystal: one intra-molecular and one inter-molecular, both involving O atoms of the meth-oxy groups. The asymmetric unit contains two independent mol-ecules not related by any pseudo-symmetry operators. The major conformational differences are localized, leading to one mol-ecule being extended compared to the other. The collected crystal was twinned (twin ratio is 0.939:0.061), and the azide group is positionally disordered over two positions in one mol-ecule [occupancy ratio 0.511 (18):0.489 (18)].